"Doing American Studies in Croatia: What Have We Done, Where Do We Go from Here?" - Šesnić, Jelena (2010)
Taking as its starting point recent developments in the field of international American studies, the author contends that when applied in a specific national context, American studies in Croatia display some peculiar departures from the generally recognized trends. In order to bolster this claim, the article then proceeds to outline several historical phases of the emergence, the application, and finally, the institutionalization of American studies in Croatia, as these responded to or deflected from the trajectory of the discipline within its native context (area studies in the wake of WW II, the Cold War consensus, “soft diplomacy, ” the role of intellectuals in the nation-state, the fall of Communism and the rise of the new Europe, the demise of the nation-state, Nine Eleven, and the globalization of American studies, among others). While some of these processes have had a decisive impact on the way American studies have been conceptualized and practiced in Croatia, it is also the case that the local context, the practitioners’ goals, immediate geo-political circumstances, and academic infrastructure have more than incidentally shaped the way American studies have subsisted in Croatia in the past fifty years.
Projekt MZOS
Projekt MZOS
ENG